The effects of intermittent hypoxic training on aerobic capacity and endurance performance in cyclists - Czuba, M.; Waskiewicz, Z.; Zajac, A.; Poprzecki, S.; Cholewa, J.; Roczniok, R. (Journal of Sports Science & Medicine, 2011)
The aim of the present study was to evaluate the efficacy of intermittent hypoxic training (IHT) with 95 % of lactate threshold workload (WRLT) on aerobic capacity and endurance performance in well-trained cyclists. Twenty male elite cyclists, randomly divided into a hypoxia (H) group (n=10; age 22 ± 2.7years; VO2max 67.8 ± 2.5 ml·kg-1·min-1; body height (BH) 1.78 ± 0.05 m; body mass (BM) 66.7 ± 5.4kg; fat free mass (FFM) 59.3 ± 5.1kg; fat content (FAT%) 11.3 ± 2.1%), and a control (C) group (n = 10; age 23.5 ± 3. 5years; VO2max 67.7 ± 2.0 ml·kg-1·min-1; BH 1.79 ± 3.2 m; BM 69.2 ± 5.5 kg; FFM 63.6 ± 4.8 kg; FAT% 7.9 ± 1.94 %) took part in the research project. The training program used during the experiment was the same for the both groups. For three weeks, the subjects in H group performed 3 training sessions per week in normobaric hypoxia environment (IHT - O2 = 15. 2%). During the elemental core of the IHT session, the intensity was set at 95% WRLT for 30-min in 1st microcycle, 35-min in 2nd microcycle and 40-min in 3rd microcycle. The same training procedure was provided in C group, yet the intensity of the main sessions were set at 100% WRLT in the normoxia environment. The results indicate a significant (p < 0.05) increase in VO2max,VO2LT, WRmax, WRLT and change in lactate concentration (?LA) during incremental test in H group. Also a significant (p < 0.05) decrease in time of the time trial was seen, associated with a significant increase (p < 0.05) in average generated power (Pavg) and average speed (Vavg) during the time trial. The intermittent hypoxic training (IHT) applied in this research did not significantly affect the hematological variables considered: number of erythrocytes (RBC), hemoglobin concentration (HGB) and haematocrit value (HCT). Significant blood value increases (p < 0.05) were only observed in MCV in H group. This data suggests that intermittent hypoxic training at lactate threshold intensity and medium duration (30-40min) is an effective training means for improving aerobic capacity and endurance performance at sea level.